2013
DOI: 10.1080/21513732.2013.788566
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of birds of conservation interest among the people living close to protected areas in Serengeti, Northern Tanzania

Abstract: We examined the ability to recognise birds of conservation interest among the residents living adjacent to the Serengeti National Park. Data on ability to recognise the photo of eight selected bird species were collected in October 2011, in relation to the respondents' gender, age, tribe and education. Almost all eight species were known by at least 50% of the respondents. The men, older people between 40 and 42 years of age and the Maasai tribe showed good or perfect ability in recognising these birds. Unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This finding may be attributed to the existing division of labour within the Maasai pastoralist society which favours males doing outdoor activities such as daily livestock herding (FAO, 2013;Mmassy & Røskaft, 2013), whereas females mostly do domestic work such as caring for children, cooking, milking livestock, fetching water and firewood collection (Mwebi, 2007). Our findings further indicate that the Maasai conflict with African wild dogs existed before their eviction from the SNP in 1959, but conflict occurred at a low level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding may be attributed to the existing division of labour within the Maasai pastoralist society which favours males doing outdoor activities such as daily livestock herding (FAO, 2013;Mmassy & Røskaft, 2013), whereas females mostly do domestic work such as caring for children, cooking, milking livestock, fetching water and firewood collection (Mwebi, 2007). Our findings further indicate that the Maasai conflict with African wild dogs existed before their eviction from the SNP in 1959, but conflict occurred at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports our hypothesis that male Maasai pastoralists have a greater awareness of local wild dog presence in their area. This is because male Maasai normally follow the livestock out into the bush (Mmassy & Røskaft, 2013) and therefore, acquire more information. Also, this finding indicates that wild dogs were present in the LGCA long before and even after the Maasai were evicted from the SNP in 1959.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that local knowledge is a powerful tool for conveying conservation information to managers (Kideghesho, 2008;Ray, Hunter, & Zigouris, 2005). Indigenous knowledge of birds in our study area has been reported to be quite high among the Maasai people (Mmassy & Røskaft, 2013). Thus, the Maasai people have previously proven to be quite knowledgeable about ability to know different wild animal species.…”
Section: Conservation Prioritiesmentioning
confidence: 76%
“…This may reduce their probability of coming into contact with wild dogs and hence limits their understanding of the species' presence in their area (see also Mmassy & Røskaft, 2013). Abram et al (2015) reported that local knowledge on endangered species should be incorporated in species conservation plans and management.…”
Section: Conservation Perceptions Under the Iucn Categoriesmentioning
confidence: 99%